PENERAPAN MODEL DISCOVERY LEARNING DALAM PEMBELAJARAN MATEMATIKA PADA POKOK BAHASAN PERSAMAAN KUADRAT PADA SISWA KELAS XI AKUNTANSI SMKN 1 PAINAN - Titi Sumarni (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2020)
One of factor that influence students achivement is the role of a teacher in the class. Teacher should be able to choose method of teaching appropriately so that it can makes the students understand the lesson fast, active in teaching and learning. In order to get a good result. Based on the observation of researcher in the SMKN 1 PAINAN, student’s ability in mathematic is low beside that, they were not interested in learning it. They were passive in the class so that the result is not good.It is important to solve the problem by doing a research. The purpose of the research is to know whether there is the influence of discovery learning model to the students’ achievement. This is an experiment research. The research used randomized control group only design. There are two classes in this research, experiment class and control class. Experiment class will be given a treatment by using discovery learning otherwise the other class will be given treatment by using convensional. Based on data analysis, it showed that score average of experiment class was 66.17, meanwhile score average of control class was 51.52. Based on the result we can conclude that teaching by using discovery learning was able to improve student achievement because in discovery learning the student find the concept by theirselves, so that it is easy for them to remember the material. They won’t be forget it easily